2016
DOI: 10.1016/j.freeradbiomed.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel RNA-binding activity of NQO1 promotes SERPINA1 mRNA translation

Abstract: NAD(P)H:quinone oxidoreductase (NQO1) is essential for cell defense against reactive oxidative species, cancer, and metabolic stress. Recently, NQO1 was found in ribonucleoprotein (RNP) complexes, but NQO1-interacting mRNAs and the functional impact of such interactions are not known. Here, we used ribonucleoprotein immunoprecipitation (RIP) and microarray analysis to identify comprehensively the subset of NQO1 target mRNAs in human hepatoma HepG2 cells. One of its main targets, SERPINA1 mRNA, encodes the seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…HNF4a is a key transcription factor upstream of a1-antitrypsin (SERPINA1) production in hepatocytes (Odom et al, 2004;Shih et al, 2000). The NQO1 protein that we observed as increased in abundance after EODF is also known to regulate the translation of the SERPINA1 mRNA (Di Francesco et al, 2016). Our EODF animals displayed a $3-fold decrease in the plasma levels of a1-antitrypsin after only 2 weeks of EODF treatment.…”
Section: Discussionmentioning
confidence: 57%
“…HNF4a is a key transcription factor upstream of a1-antitrypsin (SERPINA1) production in hepatocytes (Odom et al, 2004;Shih et al, 2000). The NQO1 protein that we observed as increased in abundance after EODF is also known to regulate the translation of the SERPINA1 mRNA (Di Francesco et al, 2016). Our EODF animals displayed a $3-fold decrease in the plasma levels of a1-antitrypsin after only 2 weeks of EODF treatment.…”
Section: Discussionmentioning
confidence: 57%
“…SERPINA1 expression is low in high-grade invasive ovarian epithelial cell carcinoma, but high in low malignant potential tumors. However, overexpression of SERPINA1 in vitro is able to promote the invasion and metastasis of tumor cells (54). For certain types of tumor, SERPINA1 is effective for treatment with target enzymes directly.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, upregulated expression of GSR is an indicator of antioxidant responses as GSR plays a critical role in the antioxidant defense not only by reducing oxidized glutathione (GSSG) but also by clearance of electrophilic metabolite (Drozd et al 2016 ). Further signs of antioxidant responses include overexpression of HMOX1, which is considered one of the most sensitive and reliable indicators of cellular oxidative stress (Maamoun et al 2016 ), TXNRD1, a pivotal intracellular redox sensor and antioxidant enzyme (Schmidt 2015 ), NQO1, which is essential for cell defense against ROS (Di Francesco et al 2016 ), and FTH1, a major iron storage protein that can protect cells from the toxic effects of iron as well as other free radical producing stresses (Funauchi et al 2015 ). In addition, downregulation of the pro-apoptotic BNIP3L, which plays an important role in hypoxia-dependent cell death (Bellot et al 2009 ) and upregulation of SQSTM1, a multifunctional adapter protein that accumulates following autophagy inhibition (Duleh et al 2016 ), was also observed.…”
Section: Discussionmentioning
confidence: 99%